Nanocellulose Extraction Using Ionic Liquids: Syntheses, Processes, and Properties - Shamsuri, Ahmad Adlie; Md. Jamil, Siti Nurul Ain; Abdan, Khalina (Frontiers in Materials, 2022)
Increased environmental awareness has encouraged researchers to seek alternatives to replace the use of hazardous chemicals in the extraction of nanocellulose for environmental conservation. Lately, ionic liquids have been used as a medium for processing cellulose and other biopolymers because they are recyclable and reusable. Recently, ionic liquids have been used to extract nanocellulose for a variety of applications. In this short review, examples of ionic liquids that are usually used for the extraction of nanocellulose are demonstrated. Additionally, sources of cellulose that are employed as raw materials for nanocellulose have also been shown. Moreover, the synthesis of ionic liquids and the process of nanocellulose extraction using ionic liquids are exhibited in this paper. In addition, the properties of nanocellulose extracted by different ionic liquids were also shortly reviewed. On top of that, the knowledge gained from this review provides a clearer comprehension of the process of nanocellulose extraction and the important properties of the extracted nanocellulose. In conclusion, this short review revealed that different mechanisms of nanocellulose extraction using ionic liquids give distinct properties to the extracted nanocellulose.